DEVELOPMENT OF HEAT AND THEMPERATURE BY USING MULTI MODUS VISUALIZATION THAT IMLEMENTED WITH GUIDED INQUIRY LEARNING MODEL TO IMPROVE CONCEPTUAL OF UDERSTANDING OF CLASS X IN SENIOR HIGH SCHOOL - Alfiah, Rani (2017)
This study aims to describe the different change of students' conceptual of understanding and students' attitude towards physics in heat and themperature by using muti modus visualization (MMV) the implemented with Guided Inquiry learning model (GI). The study conducted students' of class X in one of senior high school in Bandung regency. The tehnique of collecting data are test the students' conceptual of understanding, test students' attitude towards physics, quetionnaire of students' responses to instructional materials and obsevation sheet of implementation learning. This study use Quasi experiment two group Pretest- posttest. While the design study use embedded experimental models. The data of students' conceptual of understanding test t, tested by t test. It showes a significant different change of students' conceptual of understanding, compared students' who have learning by learning model of GI uses heat and themperature instuctional materials supported MMV compared with students' who had learning by using learning model of GI uses heat and themperature instuctional materials unsupported MMV. Level of students' conceptual of understanding at the level 3.28 it's partial understand category. As for the effect size of temperature's instructional materials supported MMV for the implementation of GI to students conceptual of understanding the capabiliting 1.5 in the category of Large effect.;---Penelitian ini bertujuan untuk mendapatkan gambaran perbedaan perubahan kemampuan memahami siswa dan profil sikap siswa terhadap fisika dalam bahan ajar suhu dan kalor (SK) menggunakan multi modus visualization (MMV) yang diimplementasikan dengan model pembelajaran Inkuiri Terbimbing (IT). Penelitian ini dilakukan terhadap siswa kelas X di salah satu SMA di Kabupaten Bandung. Tekhnik pengambilan data melalui pemberian tes kemampuan memahami siswa, tes profil sikap siswa terhadap fisika, angket tanggapan siswa terhadap bahan ajar dan lembar observasi pelaksanaan pembelajaran. Penelitian ini menggunakan Quasi experiment two group Pretest- Posttes. Sedangkan desain penelitian menggunakan embedded experimental model. Data tes kemampuan memahami siswa diuji dengan menggunakan uji t. Hasil penelitian menunjukkan adanya perbedaan perubahan kemampuan memahami siswa yang signifikan antara siswa yang mendapatkan pembelajaran menggunakan model pembelajaran IT dengan bahan ajar SK didukung MMV dibandingkan dengan siswa yang mendapatkan pembelajaran menggunakan model pembelajaran IT dengan bahan ajar SK tanpa didukung MMV. Level kemampuan memahami siswa berada pada level 3,28 dengan kategori paham sebagian. Adapun besarnya pengaruh bahan ajar SK yang didukung MMV untuk implementasi IT terhadap kemampuan memahami sebesar 1,5 dengan kategori Large Effect.